2015
DOI: 10.1145/2829988.2787475
|View full text |Cite
|
Sign up to set email alerts
|

Practical, Real-time Centralized Control for CDN-based Live Video Delivery

Abstract: Live video delivery is expected to reach a peak of 50 Tbps this year [7]. This surging popularity is fundamentally changing the Internet video delivery landscape. CDNs must meet users' demands for fast join times, high bitrates, and low buffering ratios, while minimizing their own cost of delivery and responding to issues in real-time. Wide-area latency, loss, and failures, as well as varied workloads ("mega-events" to long-tail), make meeting these demands challenging.An analysis of video sessions [32] conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 31 publications
(42 reference statements)
0
33
0
Order By: Relevance
“…The root controller periodically creates a general model of the streaming system, which is then used by the children controllers (on a coarser time-scale) to take decisions on the best QoE strategy for the video clients. A similar approach is also employed by Mukerjee et al to optimize the performance of live video streams [13]. The use of an SDN controller to optimize the behavior of HAS clients has been studied by Egilmez et al [14].…”
Section: Related Workmentioning
confidence: 99%
“…The root controller periodically creates a general model of the streaming system, which is then used by the children controllers (on a coarser time-scale) to take decisions on the best QoE strategy for the video clients. A similar approach is also employed by Mukerjee et al to optimize the performance of live video streams [13]. The use of an SDN controller to optimize the behavior of HAS clients has been studied by Egilmez et al [14].…”
Section: Related Workmentioning
confidence: 99%
“…Constraints (18)- (19) deal with the capacity of the links between leaf cache nodes and metro areas. Constraint (18) computes the amount of connections supporting each link and constraint (19) assures that the requested bitrate does not exceeds a given maximum.…”
Section: B Cdn User Reallocation (Cdn_usher)mentioning
confidence: 99%
“…Analyzing video sessions, authors in [17] concluded that a centralized controller could improve user experience, while authors in [18] introduced presented a centralized algorithm for live video optimization providing real-time, fine-grained control. In addition, placing new cache nodes to accommodate spikes in demand and consolidate workload in few cache nodes when the load decreases can also bring benefits.…”
mentioning
confidence: 99%
“…Finally, while this paper focuses on a VoD service, proactive content placement has recently been investigated in the context of live video streaming (Mukerjee et al, 2015), which focuses on the end-to-end optimization of the stream delivery. In contrast to our approach, this targets very short re-configuration intervals (in the order of milliseconds) and involves changing different parameters (e.g., video stream placement and bitrate encoding selection), which are features specific to this type of service.…”
Section: Related Workmentioning
confidence: 99%